Reduced Cardiorespiratory Fitness after Stroke: Biological Consequences and Exercise-Induced Adaptations - Sandra A. Billinger; Eileen Coughenour; Marilyn J. MacKay-Lyons; Frederick M. Ivey (Stroke Research and Treatment)
Evidence from several studies consistently shows decline in cardiorespiratory (CR) fitness and physical function after disabling stroke. The broader implications of such a decline to general health may be partially understood through negative poststroke physiologic adaptations such as unilateral muscle fiber type shifts, impaired hemodynamic function, and decrements in systemic metabolic status. These physiologic changes also interrelate with reductions in activities of daily living (ADLs), community ambulation, and exercise tolerance, causing a perpetual cycle of worsening disability and deteriorating health. Fortunately, initial evidence suggests that stroke participants retain the capacity to adapt physiologically to an exercise training stimulus. However, despite this evidence, exercise as a therapeutic intervention continues to be clinically underutilized in the general stroke population. Far more research is needed to fully comprehend the consequences of and remedies for CR fitness impairments after stroke. The purpose of this brief review is to describe some of what is currently known about the physiological consequences of CR fitness decline after stroke. Additionally, there is an overview of the evidence supporting exercise interventions for improving CR fitness, and associated aspects of general health in this population.